Antagonistic activity of phyllosphere fungi isolated from medicinal plants against Colletotrichum sp. causing anthracnose in chilli (Capsicum annuum L.) - Puspita, Ayumi Rizci; Alamsjah, Feskaharny; Mildawati, Mildawati; Agustien , Anthoni (Bioeksperimen: Jurnal Penelitian Biologi, 2026)
Anthracnose disease caused by the fungus Colletotrichum sp. is one of the main problems in chili cultivation (Capsicum annuum L.) and can cause significant yield losses. The intensive use of chemical pesticides in controlling this disease has a negative impact on the environment and health. This study aimed to evaluate the antagonistic potential of phyllosphere fungi isolated from five medicinal plants, namely Phaleria macrocarpa, Curcuma domestica, Kleinhovia hospita, Hibiscus rosa-sinensis, and Morus macroura, against the pathogen Colletotrichum sp. Isolation was performed from leaf surfaces, and a total of 7 phyllosphere fungal isolates were tested using a double culture method with three replicates. The results showed that all isolates were able to inhibit the growth of Colletotrichum sp. through mechanisms of competition for space and nutrients as well as antibiosis, with inhibition levels ranging from high to very high. Among the tested isolates, Trichoderma sp. exhibited the highest inhibitory activity with an inhibition percentage of 92.78%, categorized as very high. Macroscopic and microscopic characterization supported the identification of several isolates belonging to the genera Trichoderma. This study concluded that phyllosphere ungi from medicinal plants have the potential as environmentally friendly biological control agents in combating anthracnose disease in chili plants.